2014
DOI: 10.4103/0976-500x.124416
|View full text |Cite
|
Sign up to set email alerts
|

Diethylentriaminepenta acetic acid glucose conjugates as a cell permeable iron chelator

Abstract: Objective:To find out whether DTPA-DG complex can enhance clearance of intracellular free iron.Materials and Methods:Diethylenetriaminepentaacetic acid-D-deoxy-glucosamine (DTPA-DG) was synthesized and examined for its activity as a cell-permeable iron chelator in human hepatocellular carcinoma (HEPG2) cell line exposed to high concentration of iron sulfate and compared with deferoxamine (DFO), a prototype iron chelator. The effect of DTPA-DG on cell viability was monitored using the 3-(4,5-dimethythiazol-2-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The decreased cytotoxicity of LA–GlcN to SKOV3 cells after incubation with different concentrations of GLUT 1 inhibitor STF-31 indicated that LA–GlcN could target GLUT 1 on cancer cells and promote cell uptake (Figure a). This conclusion was in accordance with the previous reports. , Notably, the viability of SKOV3 cells after 48 h incubation with STF-31 remained at about 100% when the concentration reached 30 μM, demonstrating that STF-31 was nontoxic to SKOV3 cells up to this concentration. Subsequently, to verify that the LA–GlcN with polyunsaturated double bonds is prone to iron-dependent lipid peroxidation and induce ferroptosis, the validation tests related to ferroptosis were conducted at the cellular level.…”
Section: Resultssupporting
confidence: 93%
“…The decreased cytotoxicity of LA–GlcN to SKOV3 cells after incubation with different concentrations of GLUT 1 inhibitor STF-31 indicated that LA–GlcN could target GLUT 1 on cancer cells and promote cell uptake (Figure a). This conclusion was in accordance with the previous reports. , Notably, the viability of SKOV3 cells after 48 h incubation with STF-31 remained at about 100% when the concentration reached 30 μM, demonstrating that STF-31 was nontoxic to SKOV3 cells up to this concentration. Subsequently, to verify that the LA–GlcN with polyunsaturated double bonds is prone to iron-dependent lipid peroxidation and induce ferroptosis, the validation tests related to ferroptosis were conducted at the cellular level.…”
Section: Resultssupporting
confidence: 93%
“…To test this hypothesis, we next examined whether endolysosomal iron, as well as extracellular iron are necessary components of the morphine signaling pathway. We treated cultured neurons with morphine alone, and in the presence of DFO (100 µM, 24 h), which chelates endolysosomal iron (Doulias et al, 2003; Glickstein et al, 2005), or DTPA (100 µM, 24 h), which only chelates extracellular iron (Alcain et al, 1994; Mosayebnia et al, 2014). Importantly, DFO blocked morphine’s ability to upregulate FHC, while DTPA had no effect (Fig.…”
Section: Resultsmentioning
confidence: 99%